Examining the factors influencing Youth’s Leadership Participation in Malaysia - Simpong, Derweanna Bah; Mamun, Abdullah Al; Mohamad, Mohd. Rosli; Mat, Norsiah; Ekpe, Isidore (International Review of Management and Marketing, 2017)
This study aimed to examine the effects of social (family, friends, mentors, teachers, community leaders), political and legal influences (public policy and democratic ideas), and access and usage of social media on information and resources (leadership, community development, volunteerism, professional association, and funding), and youth’s leadership participation (extra-curricular activities, community associations, social works, political activities) under the premise of the theory of planned behavior. This study adopts the cross-sectional design and the stratified random sampling method to collect quantitative data from 400 student leaders from selected public universities, colleges, and schools in Peninsular Malaysia. Findings of this study reveal that social, political and legal influences, and access and usage of social media have a significant positive effect on information and resources; and information and resources have significant positive effects on youth’s leadership participation. To promote youth leadership participation in Malaysia, the government and development agencies should therefore focus on social and political influences, and youth’s involvement in sharing information and resources using social media. Keywords: Social Influence, Political and Legal Influence, Access and Usage of Social Media, Leadership JEL Classifications: L82, D71, D72